A gender-differentiated analysis of climate-smart agriculture adoption by smallholder farmers: application of the extended technology acceptance model. (2nd January 2021) - Khoza, Sizwile; de Beer, Leon Tielman; van Niekerk, Dewald; Nemakonde, Livhuwani
Abstract: The low adoption of climate-smart agriculture (CSA) technologies by farmers in developing regions where agrarian livelihoods are threatened by climate-related disasters remains a concerning enigma. Adoption patterns are not commensurate with merits of CSA on food security and climate resilience and attention to gender in relation to behavioral and attitudinal patterns in CSA adoption remains scarce. An exploratory-sequential mixed methods study was conducted, using a socio-psychological theoretical lens to test the applicability of the extended technology acceptance model in predicting CSA adoption among at-risk smallholder farming communities in Malawi and Zambia. Spearman's rho correlation results show that relationship strengths between socio-psychological factors—perceptions on ease of use, usefulness and climate risk—differed between men and women householdheads. Results also show that social processes are central in influencing women's decision-making on adoption. For practitioners and policy-makers, these findings reflect a critical need for gender-specific behavioral change communication strategies and inclusive participatory engagement. This will promote dialogue with diverse groups of smallholder-farmers aimed at changing negative, and leveraging on positive, behavior and attitudes toward new CSA technologies. CSA technology development for smallholder-farmers needs to appreciate the role of socio-psychological factors in adoption decisions. Further scientific research is required to establish causality between related socio-psychological factors.